DEVELOPMENT OF INTERACTIVE LEARNING VIDEOS FOR SIGEH PENGUTEN DANCE: INTEGRATING EDUCATIONAL TECHNOLOGY AND CULTURAL PRESERVATION IN MULTICULTURAL EDUCATION - Nursya Fathin Nadiya; Dwi Yulianti; Herpratiwi; Fitri Daryanti (SOSIOEDUKASI, 2026)
Learning Sigeh Penguten Dance at SMPN 38 Bandar Lampung faces several challenges, including students’ difficulties in memorizing movement sequences, synchronizing movements with rhythm, and understanding the cultural values embedded in the dance. Furthermore, learning activities are predominantly teacher-centered, limiting opportunities for independent learning. This study aimed to develop an interactive learning video for Sigeh Penguten Dance that integrates educational technology, cultural preservation, and multicultural education. The research employed a Research and Development (R&D) method using the Borg and Gall model. The participants consisted of 20 students involved in dance extracurricular activities at SMPN 38 Bandar Lampung. Data were collected through observations, interviews, expert validation sheets, student response questionnaires, and dance performance tests covering wiraga, wirama, and wirasa aspects. The results showed that the developed media achieved an average validation score of 3.90, indicating a very feasible category. Student responses reached an average of 99.7%, reflecting a highly positive perception of the media. The effectiveness test yielded an N-Gain score of 0.95, categorized as high. These findings indicate that the interactive learning video effectively improves students’ dance skills while supporting local cultural preservation and strengthening multicultural awareness through technology-based learning.